Pemanfaatan Market Place GrabFood dan GoFood dalam Peningkatan Penjualan UMKM di Kecamatan Cikarang Barat - Fitria Nurhaliza Rahmadani Putri; Etty Zuliawati Zed; Maulidia Sagita; Ummy Nur Nayla (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
With the development of digital technology, especially in the food delivery service sector, the GrabFood and GoFood platforms have become one of the solutions for MSMEs to reach a wider range of consumers without having to rely on traditional marketing methods. This research uses a qualitative method with interviews with the owners of Lumpia Beef MSMEs in West Cikarang who use both platforms. The results showed that the utilization of GrabFood and GoFood significantly helped increase sales, expand market share, and increase business visibility amidst fierce competition. However, there are challenges faced by MSMEs, such as high commission costs and competition with big brands on the same platform. This research recommends strategies to optimize the use of marketplaces, such as improving customer service, promotions, and managing operational costs, to improve the competitiveness and sustainability of MSMEs in the digital era.